Análisis por distribución de cargas de exergía a un ciclo combinado regenerativo y con recalentamiento (2018)
Exergy load distribution method is presented as a new way of calculating the overall performance of a process. This method allows relating, in a single mathematical function, the local efficiencies of a process, the thermodynamics irreversibilities of each unit operation and the primary and transformed exergy consumption. Due to in the last years the Colombian power sector has been taking importance in the country’s economic structure, a combined regenerative and reheating cycle power plant with energy capacity of 420MW has been modeled by Aspen Hyprotech Systems® V8.6 (HYSYS® V8.6) to illustrate the applicability of this method. The HYSYS´s spread sheet is used to evaluate the parameters involved in the exergy analysis. After this analysis, the load distribution method is carried out, where it is identified three primary exergy loads and one transformed exergy load in the process gas turbine. Likewise, it is identified eleven primary exergy loads and seven transformed exergy loads in the steam cycle. According to this, it is observed that the overall efficiency of gas turbine is 1.51 %, and the overall efficiency of the steam cycle is 72.05 %. It is also known that the units in which there